Alat Monitoring Kecelakaan Dengan Intelligent Transport System Berbasis Internet of Things - Junio Andika Danda; Ade Silvia Handayani; Sopian Soim; Nyayu Latifah Husni; Leni Novianti (STMIK Budi Darma, 2022)
Accidents are one of the problems that are always faced in big cities. This is evident from the indications that traffic accident numbers are always increasing. Delays in handling accidents often occur due to delays in information received by the police and nearby hospitals. Therefore, a remote monitoring system is needed to control vehicles that are operating in real time using monitoring tools that are able to detect traffic accidents and emergency events on the way In this study, the Internet of Things-based Intelligent Transport System was applied using the Support Vector Machine method whose design was carried out using accelerometer sensors, vibrating sensors and sound sensors with the addition of NEO 6M GPS as a coordinate point information provider and a PI NoIR Camera to capture images of surrounding conditions when an accident occurred. The way this tool works is that when there is an accident in a vehicle (car) this tool has been installed with various sensors and components that are able to analyze the surrounding situation if this car has an accident, it will send data that will be displayed in the Android application in the form of time data, coordinates, vibration, sound and images.